2017
DOI: 10.1002/2016ms000775
|View full text |Cite
|
Sign up to set email alerts
|

Objective tropical cyclone extratropical transition detection in high‐resolution reanalysis and climate model data

Abstract: This paper describes an objective technique for detecting the extratropical transition (ET) of tropical cyclones (TCs) in high‐resolution gridded climate data. The algorithm is based on previous observational studies using phase spaces to define the symmetry and vertical thermal structure of cyclones. Storm tracking is automated, allowing for direct analysis of climate data. Tracker performance in the North Atlantic is assessed using 23 years of data from the variable‐resolution Community Atmosphere Model (CAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 60 publications
6
48
1
Order By: Relevance
“…This is partly due to the limitations associated with objective, automated TC detection and tracking methods as well as with the definition of ET itself. In addition, a comparison of high-resolution National Center for Atmospheric Research Community Atmospheric Model hindcasts, reanalysis data, and TC best track data indicated systematic structural errors present during ET in climate models [118].…”
Section: Extratropical Transition Of Tropical Cyclonesmentioning
confidence: 99%
“…This is partly due to the limitations associated with objective, automated TC detection and tracking methods as well as with the definition of ET itself. In addition, a comparison of high-resolution National Center for Atmospheric Research Community Atmospheric Model hindcasts, reanalysis data, and TC best track data indicated systematic structural errors present during ET in climate models [118].…”
Section: Extratropical Transition Of Tropical Cyclonesmentioning
confidence: 99%
“…This method has an objective definition of ET and requires only thermal geopotential heights at isobaric levels as inputs. It has been used in a range of individual storm analyses (e.g., Bao et al, ; Griffin & Bosart, ; Liu & Smith, ; Wang et al, ; Yang et al, ) and in ET climatology studies (Kitabatake, ; Song et al, ; Wood & Ritchie, ; Zarzycki et al, ). CPS characterizes the thermal evolution of storms with three parameters: 900‐ to 600‐hPa thermal thickness asymmetry ( B ), 900‐ to 600‐hPa thermal wind (– V L T ), and 600‐ to 300‐hPa thermal wind (– V U T ).…”
Section: Methodsmentioning
confidence: 99%
“…The onset of ET is triggered when B is larger than 10 m or – V L T is lower than 0. The completion of ET is determined when the two conditions are both satisfied (Liu et al, ; Wood & Ritchie, ; Zarzycki et al, ). For HiFLOR, we employs a simplified version of the CPS method that uses 850‐ to 500‐hPa thermal thickness asymmetry ( B ), 850‐ to 500‐hPa thermal wind (– V L T ), and 500‐ to 300‐hPa thermal wind (– V U T ) due to the availability of data.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the cyclone phase space (CPS) framework proposed by Hart (2003) can be used to define ET in a purely objective, automatable way. The CPS has become widely used and has been applied to operational analysis and reanalysis data (e.g., Hart 2003; Kitabatake 2011; Wood and Ritchie 2014) as well as climate model output (Zarzycki et al 2017;Liu et al 2017).…”
Section: Introductionmentioning
confidence: 99%